2019
DOI: 10.3389/fpsyt.2019.00518
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Employment for People With Mental Illness: Results of a Multicenter Randomized Trial on the Effectiveness of Placement Budgets for Supported Employment

Abstract: Background: Individual placement and support (IPS) has proven to be effective for vocational outcomes in people with mental illness. The original concept of IPS requires temporally unlimited provision of support. Using limited placement budgets and investigating factors that predict their effectiveness may inform decisions about resource allocation. Methods: A range of patient characteristics were tested as predictors of employment outcomes in participants who attended six ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…Our results further indicated that psychosocial functioning and chronic physical illness could have an influence on the working status. The influence of psychosocial functioning and mental illness on work is in line with other studies [ 28 30 ]. In a 5-year prospective, longitudinal study based on a sample of 529 individuals with SMI who met criteria for sustained competitive employment at study entry, more than half of the participants experienced work interruptions during the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…Our results further indicated that psychosocial functioning and chronic physical illness could have an influence on the working status. The influence of psychosocial functioning and mental illness on work is in line with other studies [ 28 30 ]. In a 5-year prospective, longitudinal study based on a sample of 529 individuals with SMI who met criteria for sustained competitive employment at study entry, more than half of the participants experienced work interruptions during the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, in our cohort, despite a range of variables being considered, the only variable associated with discharge NEET status in the multivariable analysis was NEET status at service entry; supporting previous findings that baseline functioning is often the best predictor of employment outcomes (Rössler et al, 2019). We also re‐ran the model without entry NEET status, and found that SUD during treatment predicted discharge NEET status.…”
Section: Discussionsupporting
confidence: 87%
“…Some of the findings are considered contradictory. In addition to functioning, sociodemographic factors and work history [ 5 , 30 , 42 , 43 ], for example, a connection between stigma and discrimination in the workplace and employment [ 44 ] and between the type of vocational rehabilitation measure and work [ 45 ] is also described. The low values of the explained variance in our models suggest that further predictors would have an influence on the desire to work.…”
Section: Discussionmentioning
confidence: 99%